IMPLEMENTASI DAYA BERBASIS OPTIMALISASI UNTUK KAPAL DENGAN SISTEM PENGGERAK HYBRID - Muhammad Iqbal Ramadhan (2022)
This 40m high speed patrol boat operates at various speeds to fulfill its mission of protecting Indonesian waters. Mixed propulsion system is used in planning the propulsion system of 40 m High Speed Patrol Vessel. To achieve optimal performance at all ship speeds. It is a combination of mechanical propulsion system and electric propulsion system, projecting a hybrid propulsion system for 40m high speed patrol boats. The hybrid propulsion system allows the train to operate in three modes. To achieve optimal operation at the operating speed of each ship, the planning of the operating speed range of each ship must be efficient. This final project will calculate and analyze the ship's output, the main engine output needed for propulsion, the output needs of the electric motor propulsion system, the need for a motor generator, and an economic analysis of usage. A mixed propulsion system for a 40m high speed patrol boat is implemented. The results of this analysis indicate that using a hybrid propulsion system on a 40 m patrol boat achieves an efficiency of 6% better than using a mechanical propulsion system and 2% better than using an electromechanical propulsion system.